2017
DOI: 10.3390/jmse5010013
|View full text |Cite
|
Sign up to set email alerts
|

Inspection-Class Remotely Operated Vehicles—A Review

Abstract: This paper presents a review of inspection-class Remotely Operated Vehicles (ROVs). The review divides the classification of inspection-class ROVs; categorising the vehicles in order of size and capability. A state of the art technology review is undertaken, discussing various common subsystems of the ROV. Standard and novel ROV shapes and designs are reviewed, with emphasis on buoyancy, frame materials and hydrodynamics. Several power considerations and designs are discussed, accounting for battery fed and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 85 publications
0
84
0
1
Order By: Relevance
“…This is not an exhaustive list and we try to include platforms with available autonomy options (often as optional extras). A more thorough technical review of observation‐class ROVs without the discussion on autonomy can be found in Capocci et al ().…”
Section: Overview Of Autonomy For Low‐cost Observation‐class Underwamentioning
confidence: 99%
See 1 more Smart Citation
“…This is not an exhaustive list and we try to include platforms with available autonomy options (often as optional extras). A more thorough technical review of observation‐class ROVs without the discussion on autonomy can be found in Capocci et al ().…”
Section: Overview Of Autonomy For Low‐cost Observation‐class Underwamentioning
confidence: 99%
“…The demand for this type of vehicle has traditionally been driven by underwater inspection tasks such as for the oil and gas industry (Capocci et al, ), but recently the availability of these systems has started to attract a more diverse range of applications, including infrastructure inspection (Hollinger, Englot, Hover, Mitra, & Sukhatme, ), education (Deglinnocenti, ; Patterson, Elliott, & Niebuhr, ), fish stock monitoring (Chalkiadakis et al, ; Karimanzira et al, ) and marine renewable energy (Lawrance & Hollinger, ).…”
Section: Overview Of Autonomy For Low‐cost Observation‐class Underwamentioning
confidence: 99%
“…Hydraulic manipulators utilizing mineral oil as the working medium, mounted on ROV or HOV, are used for a variety of subsea tasks in different applications within offshore oil and gas, marine renewable energy and marine civil engineering industries [4] as well as in marine science and military applications [5]. As they are being used in a wide range of applications, subsea manipulators are designed for different purposes and can work at any ocean depth with the pressure compensator balancing the tank pressure with the ambient pressure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, the use of ROVs has become more widespread. This is due to the reduction in costs driven by military and oil and gas research, making the technology available for other commercial and scientific purposes [1]. In more recent years ROVs have been employed for survey contracts and, with the push in the marine renewable energy (MRE) sector, ROVs will need to be capable of operating in more difficult environments to carry out close quarters inspections of the MRE devices and structures, thus reducing operational costs within the sector.…”
Section: Introductionmentioning
confidence: 99%